Jejunal Fistula Complicating Ovarian Serous Carcinoma: Case Report of a Rare Phenomenon and Review of the Literature - Isin Ureyen; Tayfun Toptas; Sezin Ates Tatar; Gulsum Ekin; Faruk Gulec; Aysel Uysal (Gynecology Obstetrics & Reproductive Medicine)
Invasion of the wall of the digestive system by ovarian cancer cells isn’t so rare. On the other hand, fistula formation between the tumor and digestive system is an uncommon status. We described a patient with ovarian serous carcinoma that was fistulized into jejenum and formed a region composed of stool and tumor surrounded and limited by small intestines recognized during surgery. This diagnosis should be kept in mind while preparing a patient for ovarian cancer surgery if the patient has acute abdomen or abdominal pain incompatible with the extent of the tumor.